THE AMBIVALENCE OF LOVE AND HATE IN DESIRE UNDER THE ELMS: A PSYCHOLOGICAL AND MYTHOLOGICAL APPROACH - Cumhur Yılmaz Madran (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The present analysis is intended to shed some light on the psychological and mythological aspects of the ambivalence of love and hate in Eugene O’Neill’s Desire Under the Elms. The study is confined to the psychological, mythological and classical traits represented in the play. The introduction part revolves mainly around the general background information about the psychological and mythological approaches O’Neill is assumed to have used. This brief investigation is hoped to familiarise the reader with Eugene O’Neill as a modern dramatist who makes use of the classical patterns of tragedy